PWE-037 "Bear-Claw" or Over-The-Scope -Clip System (Otsc); a Breakthrough, Surgery Sparing, Endoscopic Device. (4th June 2013) - Toshniwal, J; Fry, L; Vormbrock, K; Zabielski, M; Mönkemüller, K
Abstract : Introduction: The "bear-claw" or over-the-scope clip system, OTSC (Ovesco Endoscopy, Tübingen, Germany) is a new clipping device developed for closure of large luminal gastrointestinal (GI) defects. Methods: To evaluate the clinical outcomes of patients treated with the OTSC a prospective, single-arm, pilot study was conducted in a regional hospital with tertiary care endoscopy. This study involved 11 clip applications in 10 patients (median age 76.2 years [range 52–89 years], 5 women) with GI defects from fistulas and anastomotic dehiscence and peptic ulcer bleeding. Results: Bleeding posterior duodenal wall ulcers (n = 4), bleeding gastric ulcer (n = 2), three fistulas or anastomotic dehiscences (n = 4) were treated using the OTSC-system. In addition a self-expanding metal stent was anchored securely in place with an OTSC-system. The diameter of ulcers and/or leaks ranged between 12 and 20 mm. A complete sealing of leaks was achieved in 3/4 patients. There were no clip complications. However, during introduction of the loaded clip on the tip of the endoscope, the hood tended to migrate over the scope, i.e. retracting, thus diminishing the exposed hood. This leads to diminished tissue suction and closure. Thus we modified the technique by tightly taping the hood on the tip of the scope. This trick may explain why all our cases were successful. Conclusion: The OTSC system is a useful device in a variety of clinical scenarios including the management of larger GI leaks, GI bleeding and stent anchoring, even in very old and frail patients. Disclosure of Interest: None Declared.